2015
DOI: 10.1111/bcpt.12384
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Carnitine Enhances Bone Fracture Healing under Osteoporotic and/or Inflammatory Conditions

Abstract: The aim of this study was to examine the effects of carnitine on bone healing in ovariectomy (OVX) and inflammation (INF)-induced osteoporotic rats. The rats were randomly divided into nine groups (n = 8 animals per group): sham-operated (Group 1: SHAM); sham + magnesium silicate (Mg-silicate) (Group 2: SHAM + INF); ovariectomy (Group 3: OVX); ovariectomy + femoral fracture (Group 4: OVX + FRC); ovariectomy + femoral fracture + Mg-silicate (Group 5: OVX + FRC + INF); ovariectomy + femoral fracture + carnitine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…One of these cytokines is IL-6, which is known as a crucial factor for the recruitment of inflammatory cells [41, 72]. In addition, several studies demonstrated increased IL-6 expression after tissue injury in oestrogen-deficient mice [15, 16]. In the present study, we found higher IL-6 expression in the periosteal cells of OVX-mice.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…One of these cytokines is IL-6, which is known as a crucial factor for the recruitment of inflammatory cells [41, 72]. In addition, several studies demonstrated increased IL-6 expression after tissue injury in oestrogen-deficient mice [15, 16]. In the present study, we found higher IL-6 expression in the periosteal cells of OVX-mice.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the immune response is altered when the system is challenged. For example, the inflammatory response was increased in oestrogen-deficient mice after induction of paw inflammation or rheumatoid arthritis [1517]. During wound healing, pro-inflammatory cytokines were up-regulated in rodents subjected to ovariectomy (OVX), resulting in delayed skin repair [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…S1 , A and B). As a previous study has established, interruption of estrogen is associated with the inflammatory process in bone, featured by increasing pro-inflammatory cytokines 22 . The expressions of TNF- α and IL 1-β in serum were compared between sham and OVX mice, and implied an inflammatory skeletal microenvironment in OVX mice (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The skeletal and immune systems are closely linked, as shown in postmenopausal osteoporotic females and estrogen-deficient rodents [ 6 , 7 , 8 , 9 , 36 ]. In addition, the immune response to injury is altered under estrogen-deficiency [ 10 , 11 , 13 , 37 , 38 ]. Regarding fracture healing, OVX-mice displayed increased systemic serum Mdk levels on day 10 after fracture [ 39 ], increased local Mdk and IL-6 expression and more neutrophils on day 3 in the fracture callus, thus indicating a misbalanced immune response after fracture under estrogen-deficient conditions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%